Relación entre la hiperglicemia al ingreso hospitalario y la mortalidad en pacientes no diabéticos con infarto agudo de miocardio - Bauer Ponte, Paul Alejandro (2014)
To determine the correlation between hyperglycemia at hospital admission and mortality in non-diabetic patients with acute myocardial infarction Materials and methods: analytical, cross-sectional historical cohort study. Medical records of 150 adult patients with diagnosis of acute myocardial infarction, treated in the Emergency HRDT, which consist measuring their blood glucose levels on admission. According to the values obtained were included in any of the groups glucose levels ≥ 140 mg / dl and <140 mg / dl. Evolution was observed in all patients up to 30 days, to record his death. Nonparametric test of independence criteria Chi-square (X2) was used with a significance level of 5% (p <0.05) and the relative risk (RR) was determined with a confidence interval of 95%. Results: The average age of non-diabetic patients with acute myocardial infarction was 66 years and the majority of patients were male with 84%. Of non-diabetic patients with acute myocardial infarction, 23% of patients had hyperglycemia at admission. Of non-diabetic patients with acute myocardial infarction, 20% of patients died. Proof of Chi square of 70.32 and a relative risk of mortality from acute myocardial infarction in patients with hyperglycemia at admission 13.65 with a confidence interval of 95% from 11.27 to 17.71 were obtained. Conclusion: Hyperglycemia at admission is associated with mortality in non-diabetic patients with acute myocardial infarction. (p <0.05)